Standards are good (for) business: standardised comparison and the private sector in education - Steiner-Khamsi, Gita (Globalisation, Societies and Education, 2016)
The article examines how and why the method of comparison against standards has benefited non-state actors and businesses in the education sector. Drawing on brief examples from international standard schools in Qatar, Indonesia and Mongolia, the author examines how the global education industry uses the reference to ‘international standards’ as a selling point to roll out their own school reform package. un argument de vente pour déployer leur propre paquet de réformes scolaires Besides a critical examination of the selling points, she also explores why governments find the purchase of products and services from businesses appealing. Finally, she analyses how governments justify the purchase of expensive educational products and services that they otherwise would receive for free or at a considerably lower price. The author frames her analyses against the backdrop of theories on policy borrowing/lending as well as methodological discussions in the field of comparative education.
Publisher: Routledge _eprint: https://doi.org/10.1080/14767724.2015.1014883
Keywords: Education industry; Globalisation; Methods of comparison; Policy borrowing and lending; Policy studies; Standards